The Albanian name for badger - Witczak, Krzysztof Tomasz (Zeitschrift für Balkanologie, 2012)
The traditional etymology, according to which the Albanian term for ‘badger’, vjédhull(ë), derives from the verb vjedh ‘to steal, to rob’, seems doubtful from both a phonological and semantic point of view. A new hypothesis, which refers to IE. *wes- ‘suet, lard, animal fat’ and especially to Iran. *vasdah- n. ‘animal fat’ (< IE. *wes-d[h]-es-), is suggested. Finally, it is concluded that Alb. vjédhull(ë) and Roum. viezure ‘badger’ derives from IE. *wesd[h]-ulā f. (liter. ‘fat animal’).